Novel Electrosurgical Bailout Technique for Acute Left Main Occlusion Post Redo–Transcatheter Aortic Valve Replacement in a Surgical Bioprosthesis: A New Arsenal in a Structural Interventionalist's Armamentarium. (April 2021) - Nagaraja, Vinayak; Krishnaswamy, Amar; Reed, Grant; Yun, James; Kapadia, Samir R.
Abstract : Supplemental Digital Content is available in the text.